The institutionalization of primary and secondary public instruction in the Parahyba do Norte Province (1836 -1849) - Cristiano de Jesus Ferronato; Mauricéia Ananias (Acta Scientiarum. Education, 2015)
This text AIMS at analyzing the process of institutionalization of primary and secondary public education in the Parahyba do Norte Province between 1836-1849 and also and links this movement with government initiatives and possible relationships with the subjects of instruction in the period. Using sources such as regulations for Education enacted on the 15th and the 20th of January, 1849, respectively; and the statutes of the Provincial Lyceum enacted in 1846; it is compared the reports of the Province Presidents and the various documents on Education, with the analytical intention of understanding the government initiatives as well as the responsibilities assigned to teachers as responsible for the organization and class maintenance. We conclude that the form of organization for methods, the behavior of teachers and the supervision and control by the provincial government announced in the regulations and statutes, intended gradually to standardize the teaching and to build spaces of schooling for part of  Paraiba population.